Precise levelling data processing near terraced landforms - Talvik, Silja (Geodesy and Cartography, 2014)
Precise levelling results are affected by the Earth’s gravity field, especially in areas of abrupt changes of landscape, such as terraced landforms. To eliminate the effect of the gravity field gradient, corrections need to be used in precise levelling data processing. To estimate the expected range of the correction due to the gravity field gradient (here called the gravimetric correction) within a region of terraced landforms, an experiment was proceeded in Estonia. Gravity data together with GNSS coordinates were acquired in 2011 in an area where a levelling section crosses the North Estonian Klint (height difference of 30 m within the levelling section). The gravimetric correction for the given 300 m long section proved to be 1.2 mm. Practically the same correction value can be obtained using interpolation of existing gravity data. However, in the case study area the gravity database had an extremely good quality which may not be the case elsewhere in which case gravimetric information needs to be collected alongside levelling. In height network calculations it is important to note that in such challenging areas all points should obtain their height values from an adjustment or from a point on the same side of a terrace, otherwise errors in heights may be as large as the gravimetric correction across the terrace.